"The State" of International Studies: Curriculum Design. Issue 2 (April 2020) - Gentry, Bobbi; Stojek, Szymon
ABSTRACT: In recent decades, institutions across the United States have increasingly emphasized global education as a prerequisite to successful existence in a diverse yet interconnected world. At the same time, there is increasing awareness that the decline in international studies (IS) has resulted in the United States being ill prepared to address complex global challenges. King (2015 ) lamented that the United States now increasingly lacks regional experts who understand the country-specific challenges and can place them in a larger global strategic context. How the discipline engages students in a global environment matters; however, the field provides little guidance on how to design global studies majors. IS and global studies are apparently both important and neglected. This study examines the curricula for IS, international relations, international affairs, and global studies programs housed in political science. By reviewing more than 100 programs that offer bachelor's degrees, the authors identify similarities and differences in curricula and present a summative model of a typical IS program housed in political science departments.